Correlation of the GC-MS-based metabolite profile of Momordica charantia fruit and its antioxidant activity - V., Perumal; A., Khatib; Q. U., Ahmed; B. F., Uzir; F, Abas; S., Murugesu; M. Z., Saiman; R., Primaharinastiti; H., El-Seedi (UPM Press, 2022)
Momordica charantia or bitter melon (Cucurbitaceae) is a widely consumed edible fruit with strong antioxidant properties. Due to these properties, it has been commercialised by the natural product industries as a coadjutant in the treatment of various ailments attributable to the deleterious effects of oxidants. The present work aimed to evaluate the antioxidant activity of M. charantia fruit extracts made with different compositions of ethanol:water, and to identify the metabolites that are responsible for this activity. To this end, the fruit samples were extracted using six different concentrations of ethanol in water (0, 20, 40, 60, 80, and 100%). Gas chromatography-mass spectrometry (GC-MS) and multivariate data analysis (MVDA) were used to identify significant antioxidants. The 80% ethanol:water extract showed the most significant (p < 0.05) antioxidant activity when tested with the 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) antioxidant assays. The multivariate data analysis revealed that the metabolites related to this antioxidant activity were gentiobiose, glucose, galactonic acid, palmitic acid, galactose, mannose, and fructose.